PERSEPSI MAHASISWA TERHADAP PENGAMANAN UNJUK RASA (DEMONSTRASI) YANG BERAKHIR BENTROKAN ANTARA APARAT DAN MAHASISWA DI PEKANBARU TAHUN 2019 - Haritsi, Ahmad Al; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In accordance with the mandate of the law, all demonstration activities will always coexist with the police. Dealing with the police as providing services that provide facilities for demonstrations for students is indeed a common thing. The problem is that so far the security protests provided have often failed to meet the expectations of students. Many parties view that the methods of officials in the field often cause controversy. Perception is a form of public response as service recipients that can illustrate the success of the efforts that have been made, so that it can be a measure of the extent to which the given authority has been implemented.This study aims to describe the implementation of the police's duties in exercising their authority to secure demonstrations through Student Perceptions of Protecting Protests (demonstrations) by the Police, which ends in clashes between apparatus and students in Pekanbaru in 2019. This research uses qualitative descriptive methods and collection techniques. data based on observation, literature study and interviews.Students' perceptions of the security of demonstrations by the Police in Pekanbaru were greater towards negative perceptions, this could be proven that when the clashes occurred, the police could not control the situation because the large number of protesters still caused victims and damaged several public facilities to damage officer vehicle. From the research results, the factors that most play a role in shaping students' perceptions of protest security by demonstration security officers are the student's own experience factors and the experiences they hear and see from those around them.Keywords: Student Perception, Protest Security